2008
DOI: 10.4012/dmj.27.368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Osteogenic Potential Between Apatite-Coated Poly(Lactide-Co-Glycolide)/Hydroxyapatite Particulates and Bio-Oss

Abstract: Previously, we developed a poly(lactide-co-glycolide)/nano-hydroxyapatite (PLGA/HA) composite that overcame the limitations of conventional ceramic bone substitutes. This was achieved by introducing a bone-like apatite layer on the composite to further enhance its osteogenic potential. In this study, we compared the osteogenic potential of the apatitecoated PLGA/HA particulates to that of Bio-Oss ® , a deproteinized bovine bone material. A mixture of fibrin gel and either apatite-coated PLGA/HA particulates or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Skeletally mature rats (We use inbred Fisher 344 rats, 11–12 week old, male, Harlan, catalog number F344/NHsd; however, inbred Lewis 34 and outbred Sprague-Dawley 28,30,35 and Wistar 25 rats have been used. )…”
Section: Methodsmentioning
confidence: 99%
“…Skeletally mature rats (We use inbred Fisher 344 rats, 11–12 week old, male, Harlan, catalog number F344/NHsd; however, inbred Lewis 34 and outbred Sprague-Dawley 28,30,35 and Wistar 25 rats have been used. )…”
Section: Methodsmentioning
confidence: 99%
“…This same study also showed that the nanocrystal hydroxyapatite easily adhered to the fibroblasts and osteoblasts of the periodontal ligament (17). Porosity, surface structure, particle size and chemical features have are key characteristics that dictate the regenerative and osteoconductive potential of bone substituents (18). Thus, the greater treatment efficacy of Biohapel that we observed was most likely a consequence of the specific features of the material.…”
Section: Discussionmentioning
confidence: 57%
“…The initially higher relative expression of Spp1 in the B group could be attributed to the osteoconductive nature of Bio-Oss Ò : it 'attracts' resident progenitors, [29] thus building a 'framework' for blood vessels and bone-forming cells. [30] However, the relative expression of Spp1 was more sustainable in EPB implants compared to PB and B ones, which might be related to interaction that occurs between secreted osteopontin and ECs. Soluble osteopontin has an anti-apoptotic effect on adherent ECs [31] and it can, therefore, be presumed that an impact on sustainable vascularization and osteogenic process in EPB implants can be achieved through this mechanism.…”
Section: Mm_vcam1_1_sg Qt00128793mentioning
confidence: 92%